Digitalization of Micro, Small and Medium Enterprises And Its Implications for Social Mobility - Hidayat, A. Taufiq; Khalilah Daud Isaac Makhmut; Laila Nur Azizah (Universitas Kristen Cipta Wacana, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy. However, challenges such as limited market access and resources often hinder their development. Digitalization is one solution to improve competitiveness and social mobility. Micro, Small, and Medium Enterprises (MSMEs) are productive businesses owned by individuals or small business entities with certain limitations in terms of assets and turnover, in accordance with Law Number 20 of 2008 concerning Micro, Small, and Medium Enterprises (MSMEs). They serve as the backbone of the Indonesian economy, contributing significantly to Gross Domestic Product (GDP) and providing employment. MSMEs still face various challenges, such as low digital literacy and difficulties in marketing and product innovation. The use of technology can be a solution for MSMEs to increase competitiveness and expand markets. This study aims to analyze the role of digitalization in driving the development of Micro, Small, and Medium Enterprises (MSMEs) and its implications for social mobility of entrepreneurs. This study uses a qualitative method with case studies of several MSMEs that have implemented digitalization. Data were collected through in-depth interviews with MSME owners and analysis of related documents. Digitalization is understood as the use of digital technology, particularly e-commerce platforms, social media, and digital financial services, which can open wider market access, increase business efficiency, and strengthen competitiveness. Using a qualitative approach and in-depth interviews with MSMEs, this study found that digitalization contributes significantly to increased income, expanded social networks, and changes in the socioeconomic status of the community. However, the study also revealed gaps in access to technology and digital skills that can widen the social gap between adaptive MSMEs and those left behind. The results of this study indicate that digitalization functions not only as an economic instrument but also as a crucial factor in encouraging social mobility, provided there is support from policies and programs to improve sustainable digital literacy